Dampak Operasional PLTU terhadap Kondisi Sosial Ekonomi Nelayan: Studi Kasus Kelurahan Teluk Sepang - Tri Elvina Damayanti; Ishak Fadlurrohim; Yessilia Osira (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Industrial development in coastal areas through the construction of a Steam Power Plant (PLTU) has significant economic implications for the sustainability of fishermen's livelihoods. This study aims to analyze the impact of PLTU operations on the socio-economic conditions of fishermen in Teluk Sepang Village, Bengkulu City. This study used a qualitative descriptive approach with a snowball sampling technique, involving 26 small-scale and traditional fishermen directly affected. The results indicate that damage to the coastal ecosystem due to PLTU activities reduces water quality and the availability of fish resources, resulting in decreased catches and income instability. Fishermen are forced to venture farther out to sea, incurring increased operational costs, further putting pressure on household economic conditions. This economic pressure exacerbates fishermen's vulnerability due to limited capital and high dependence on marine resources. Fishermen's adaptation strategy involves diversifying their livelihoods into non-fishing sectors, such as laboring to supplement household income. Changes in social conditions are reflected in the decline in fishermen's solidarity, marked by a weakening of mutual cooperation (gotong royong) and a reduction in collective cooperation due to economic pressures. This study demonstrates that PLTU operations impact the socio-economic structure of fishermen, necessitating sustainable protection and empowerment policies for coastal communities.